Catalytic oxidation of NO at ambient temperature over the chars from pyrolysis of sewage sludge. (July 2020) - Deng, Wenyi; Tao, Cong; Cobb, Kirk; Zhou, Hongfeng; Su, Yaxin; Ruan, Roger
Abstract: Sludge char (SC) was prepared by pyrolysis of sewage sludge, then nitric acid washing, potassium hydroxide activation, and hydrogen reduction methods were used to seek for the optimum treatment for improving the catalytic oxidation of NO at 30 °C. The optimum NO conversion of 65.6% was achieved when SC was activated and hydrogen-reduced, indicating the promising prospect of NO oxidation catalyst preparation from sewage sludge. The prepared SCs showed an intensive specific pore volume peak at the micropore size of 0.89 nm which is beneficial for NO oxidation. SC characterization like temperature programmed desorption of CO2 /NO/NO2, in-situ diffuse reflectance infrared Fourier transform spectroscopy, etc. were conducted to reveal the catalytic oxidation mechanisms of NO. The results indicated that the oxygen-containing functional groups, such as carboxylic acid, carboxylic anhydrites and lactones, were largely removed by hydrogen reduction, leading to marked increases of surface basicity, specific surface area, and catalytic activity of SCs. The NO oxidation over the SCs can be explained quite well by the Eley-Rideal reaction model. Graphical abstract: Image 1 Highlights: The best NO conversion of 65.6% was achieved over sludge derived catalyst. The increase of micropore volume showed positive effect on NO oxidation. Oxygen functional groups in sludge char showed negative effect on NO oxidation. NO oxidation mechanism can be well explained by the Eley-Rideal model.